Mitochondrial neuropathy in pediatric patients carrying mtDNA, POLG1, SURF1, and PDHA1 mutations - Finsterer, MD, PhD, Josef; Zarrouk-Mahjoub, PhD, Sinda (Journal of Medical Biomedical and Applied Sciences, 2018)
see the pdf.